Drawing the spiritual. The churches of Álvaro Siza Vieira - Guilherme, Pedro (2020)
Álvaro Siza Vieira is one of the most well-known Portuguese architects. The inscription of an ensemble of work of Álvaro Siza Vieira at the National Tentative List for World Heritage gives testimony of the complementary, transdisciplinary and varied views that his architecture can touch many themes, including the complexity of the spiritual religious space. Drawing, as well as competitions, is used by ASV as means of researching "for" (research-based design), "into" (research analysing how design works) and "through" (design-based research which also include design through research) architecture. It is both a method and a record fixing his quest for the wholeness. This paper will focus on the churches that were esigned by Siza, in particular their drawings, as they transcend the physical world towards the mystery of the faith and soul, following the research pursued about the neighbourhood of Malagueira (1977- 2005). Thus the paper will focus on the first church and parochial centre of São João Bosco in Malagueira (1988-89) never built, the Santa Maria church in Marco de Canavezes (1990-2006), the Santa Maria de Rosario church in Rome (1998- 2000) and the new Church of Saint-Jacques de la Lande in Rennes (2018). We will focus on the process and research "for", "into" and "through" the project and on the discussion of the fundamental themes of past and present, conservation and contemporaneity as the Angelus Novus floats in some of Siza's drawings. The paper will address light and shadow, form and matter, the intangible presence and character of god, the discussions and contradictions of theological interpretations in the functions of liturgy for each project. But also convey the closeness with the community and its linkage to both site and place, as building becomes a part of the territory/landscape in a close relation between church and community.